Phytochemical, acute toxicity, analgesic, in vitro antioxidant studies and GC-MS investigation of essential oil of the methanol leaf extract of Momordica charantia (2017)
Medicinal plants have bioactive compounds which play an important role in the healing of various diseases. They are the best sources for chemical ingredients, antimicrobial and antioxidant agents for cure of different diseases. Most medicinal plants possess pharmacological activities (anti-inflammatory, antidiabetic, antioxidant, antibacterial, antifungal etc.) due to the presence of these phytochemicals in them. In this study, we intend to conduct qualitative phytochemical screening and to quantitatively evaluate the total phenol, flavonols, tannins, proanthocyanidins and flavonoids contents of the plant, Mormodica charantia. The acute toxicity studies of the methanol leaf extract of M. charantia on mice was conducted to evaluate how safe the plant is in relation to dosage, and this is intended to establish the safety of the plant in mice with reference to OECD guidelines. Furthermore, the analgesic activity of the methanol leaf extract of M. charantia and the free radical scavenging activities of the plant in vitro were demonstrated using various standard procedures. We also intend to profile the major compounds present in the essential oil of the plant understudied using Gas Chromatography-Mass Spectrometry Analysis. Summarily, this study was aimed to investigate the phytochemical screening, acute toxicity, analgesic, in vitro antioxidant, as well as the chemical constituents in the essential oil of the methanol leaf extract of M. charantia.